Dynamic positioning of ships with unknown parameters and disturbances. (July 2018) - Du, Jialu; Hu, Xin; Krstić, Miroslav; Sun, Yuqing
Abstract: Robust adaptive control is proposed for the dynamic positioning (DP) of ships with unknown model parameters and unknown time-varying disturbances. Through representing the parameter uncertain ship motion mathematical model and the unknown time-varying disturbances as parametric forms, respectively, constructing an observer for handling disturbances, and using the adaptive vectorial backstepping, the DP robust adaptive control law is designed. The proposed DP control law achieves the global asymptotic regulation of positioning errors, while guaranteeing the global uniform ultimate boundedness of all signals in the DP closed-loop control system. Simulation results involving a supply vessel validate the proposed DP control law. Highlights: Robust adaptive control for the DP of ships is proposed. No a priori knowledge of ship dynamic model parameters and disturbances is required. Unknown time-varying disturbances are online estimated using observer and adaptive technique. Global asymptotic regulation of the positioning errors is achieved.